PSYCHOLOGICAL AND LINGUISTIC BARRIERS TO ORAL SPEECH AMONG ENGLISH LANGUAGE LEARNERS (SCIENCE TIME JOURNAL, 2026)
Oral communication is a key indicator of language proficiency, yet many English language learners face persistent challenges in developing effective speaking skills. This article investigates the psychological and linguistic barriers that impede oral speech among English language learners. Psychological factors such as speaking anxiety, fear of making mistakes, low self-confidence, and reduced motivation are examined as major constraints on learners’ willingness to communicate. In parallel, linguistic barriers—including limited vocabulary, grammatical interference, pronunciation difficulties, and inadequate exposure to authentic spoken English—are analyzed for their impact on speech production. The study draws on classroom observations, learner feedback, and established theories in second language acquisition to illustrate how these psychological and linguistic factors interact and reinforce one another. The findings emphasize the need for an integrated pedagogical approach that combines emotional support with communicative and linguistically focused instruction. The article concludes by offering practical recommendations for educators to reduce speaking anxiety and improve oral competence in foreign language learning contexts.